Avaliação do desempenho de mantas sintéticas não tecidas no tratamento de água para consumo humano visando utilização em comunidades rurais: ensaio em escala piloto - Helder Albino Cumbi (2013)
The aim of this research is to increase the alternative potentiality of water treatment for human consumption in rural communities. Thus, was built a pilot plant for water filtration in blanket woven synthetic nonwoven. The blanket used was chosen as from the results obtained in preliminary tests which covered eight blankets. The M8 blanket with 1200 g/m² of weight presented higher significant capable of impurities removing than the others at a significance level of 5%. The water with 10, 50 and 100 NTU (Type I, Type II and Type III, respectively) was filtrated using M8 blanket at three different filtration rates of 5; 20 and 50 m³.m-².d-¹, for testing without coagulation and 20, 50 and 100 m³.m-².d-¹ for testing with coagulation and the period of monitoring was twelve hours for each test. The results showed that combined the Type I without coagulation with low filtration rate (5 m³.m-².d-¹) was obtained production of effluent with many values of turbidity less than 5.0 NTU. However, in Type III water with filtration rate of 20 m³.m-².d-¹, was observed a rapid maturation of the filtration media, this can be justified by the low effluent turbidity and significant head loss recorded in the short time of operation. On the other hand, when the raw water has previously been coagulated, the blanket possible to obtain results remaining turbidity less than 0.5 NTU at all rates tested, thus having the maximum established acceptable for drinking water in Brazil that according to the decree 2914/2011 MS poses as maximum turbidity of 0.5 NTU and 1.0 NTU for rapid filtration and slow sand filtration, respectively by the end of the fourth year from the date of publication (12/12 / 2011). Nevertheless, the main obstacle to use this blanket was the smallest careers filtration, around four hours, which verified in tests involving the filtration rate of 100 m³.m-².d-¹. The filtration rate of 20 m³.m-².d-¹ had greatest careers filtration which exceeded the twelve hours. It is noteworthy that the rate of 50 m³.m-².d-¹ for value of lost head of 80 cm was more efficient for the filtration of coagulated water, once produced most effective water compared with other filtration rates. This research proved the potential of the use of non-woven synthetic blanket in the treatment of water with high turbidity, but it becomes necessary to develop other research to improve this technique.